The Development of Political Theatre in Turkey - Özlem ÖZMEN (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
The use of political subjects in Turkish theatre is first observed in theatre-inthe-round in folk drama. As political theatre makes progress during the Tanzimat Reform Era in Turkey, it gains importance with transition periods such as the proclamation of the Turkish Republic and the development of the multi-party system. It was in the 1950s and 1960s when social unrest was unignorable that works of political theatre were most written. The development of political theatre depends on the political events of the period in which it is produced. For instance, while plays written in the Tanzimat Reform Era and the Period of Autocracy depict the oppression of Sultan Abdülaziz, the liberation of art is reflected in the works produced during the Second Constitutional Era. Following this period, political theatre displays the transition period experienced by a divided society with the declaration of the Republic. In the political theatre of the 1950s and 1960s, civil unrest resulting from social disorder is in the foreground. Although some theatre groups still continue dealing with political issues in our day, political theatre, which has regressed after 1971 memorandum and 1980 coup d’etat, seems to have lost its former efficiency.